Capability of Updating the List of Permanent Voters by Pekanbaru Election Commission During 2019 Election - Rury Febrina; Friska Amanda; Jastika Nofriyanti; Juni Yulfiyanti Hutabarat (JOELS: Journal of Election and Leadership, 2020)
This article discusses the problem of double voter lists in Pekanbaru. General Elections Commission (KPU) Pekanbaru set 3.62 Million Final Voter List (DPT), and Election Supervisory Agency (Bawaslu) found 1,956 double DPT. The problem of double DPT is seen from the aspect of updating data from the KPU Pekanbaru in the process of determining the number of DPT through stages of matching and research (coklit). This study uses descriptive qualitative methods with informants determined by researchers. The informant for this research is KPU Pekanbaru. The data obtained have been analyzed with an ethical and emic approach to finding that the double DPT was caused by the coklit process, which was not optimally conducted by Pekanbaru's KPU. The coklit process was hampered because voters were not at their place, so the KPU only relied on data from the neighbourhood (RT).